2014
DOI: 10.1128/jvi.02851-13
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathological Influenza A Virus Infection Is Associated with Augmented Expression of PD-1 by Functionally Compromised Virus-Specific CD8+T Cells

Abstract: One question that continues to challenge influenza A research is why some strains of virus are so devastating compared to their more mild counterparts. We approached this question from an immunological perspective, investigating the CD8 ؉ T cell response in a mouse model system comparing high-and low-pathological influenza virus infections. Our findings reveal that the early (day 0 to 5) viral titer was not the determining factor in the outcome of disease. Instead, increased numbers of antigen-specific CD8؉ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 56 publications
10
77
0
Order By: Relevance
“…These data are in line with recent reports of PD-1 expression on lung T cells during influenza and HMPV infection. 2426 Interestingly, we further found that PD-1 is highly upregulated on IL-10 producing effector T cells, suggesting that IL-10 and PD-1 expression in T cells may be regulated by the same molecular machinery during RSV infection. Notably, we recently showed that the transcription factor Blimp-1 promoted IL-10 production by effector T cells during influenza infection.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…These data are in line with recent reports of PD-1 expression on lung T cells during influenza and HMPV infection. 2426 Interestingly, we further found that PD-1 is highly upregulated on IL-10 producing effector T cells, suggesting that IL-10 and PD-1 expression in T cells may be regulated by the same molecular machinery during RSV infection. Notably, we recently showed that the transcription factor Blimp-1 promoted IL-10 production by effector T cells during influenza infection.…”
Section: Discussionmentioning
confidence: 58%
“…23 Recently, it was demonstrated that the blockade of PD-1 and PD-L1 interaction in vivo resulted in elevated host effector T-cell responses and enhanced viral clearance during influenza and human metapneumovirus (HMPV) infection, suggesting that PD-1 and PD-L1 may also play a role in restricting effective anti-viral T-cell responses during acute viral infections. 2426 Similarly, in an in vitro co-culture model, the PD-L1/PD-1 interaction has been shown to inhibit CD8 + T cell effector function when encountering RSV-infected human epithelial cells. 27 However, the exact function of PD-1 and its ligands in vivo during RSV infection, particularly within the respiratory tract, is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Titers of infectious virus were measured by plaque assay on monolayers of Madin-Darby canine kidney (MDCK) cells as previously described (44).…”
Section: Methodsmentioning
confidence: 99%
“…Introduction E ach year, emerging influenza A virus (IAV) infections hospitalize 3-5 million individuals (30), posing a major health threat and significant economic burden worldwide. In addition to circulating seasonal strains, natural IAV infections in zoonotic reservoirs undergo antigenic drift (12,13) and antigenic shift (19) that efficiently evade host immune responses and cause extensive morbidity when transmitted to humans.…”
mentioning
confidence: 99%